Prescription pattern and effectiveness of antihypertensive drugs in patients with aortic dissection who underwent surgery - Liao, Kuang-Ming; Shen, Chuan-Wei; Huang, Yun-Hui; Lu, Chun-Hui; Lai, Hsuan-Lin; Chen, Chung-Yu (Frontiers in Pharmacology, 2023)
Surgical patients with aortic dissection often require multiple antihypertensive drugs for blood pressure control. However, the prescription pattern and effectiveness of antihypertensive drugs for these patients are unclear. We aimed to investigate the prescription pattern and effectiveness of different classes of antihypertensive drugs in surgical patients with aortic dissection.Newly diagnosed aortic dissection patients who underwent surgery, aged > 20 years, from 1 January 2012 to 31 December 2017 were identified. Patients with missing data, in-hospital mortality, aortic aneurysms or congenital connective tissue disorders, such as Marfan syndrome, were excluded. Prescription patterns of antihypertensive drugs were identified from medical records of outpatient visits within 90 days after discharge. Antihypertensive drugs were classified into 4 classes: (1) β-blockers, (2) calcium channel blockers, (3) renin-angiotensin system and (4) other antihypertensive drugs. Patients were classified according to the number of classes of antihypertensive drugs as follows: (1) class 0, no exposure to antihypertensive drugs; (2) class 1, antihypertensive drugs of the same class; (3) class 2, antihypertensive drugs of two classes; (4) class 3, antihypertensive drugs of three classes, or (5) class 4, antihypertensive drugs of four classes. The primary composite outcome included rehospitalization associated with aortic dissection, death due to aortic dissection, and all-cause mortality.Most patients were prescribed 2 (28.87%) or 3 classes (28.01%) of antihypertensive drugs. In class 1, β-blockers were the most commonly used (8.79%), followed by CCBs (5.95%). In class 2, β-blockers+CCB (10.66%) and CCB+RAS (5.18%) were the most common drug combinations. In class 3, β-blockers +CCB+RAS (14.84%) was the most prescribed combination. Compared to class 1, class 0 had a significantly higher hazard of the composite outcome (HR, 2.1; CI, 1.46-3.02; P<0.001) and allcause mortality (HR, 2.34; CI, 1.56-3.51; P<0.001). There were no significant differences in hazards for rehospitalization associated with aortic dissection among classes.Among operated patients with type A aortic dissection, no specific type of antihypertensive drug was associated with a better outcome, while among those with type B aortic dissection, the use of β-blockers and CCBs was related to a significantly lower risk of the composite outcome.